Effect of Rhizoma Paridis saponin on the pain behavior in a mouse model of cancer pain. Issue 31 (9th May 2018) - Wang, Genbei; Liu, Yuanxue; Wang, Yu; Gao, Wenyuan
Abstract : Rhizoma Paridis saponins (RPS) as active parts of P. polyphylla Smith var. yunnanensis has been used as an anti-cancer drug in traditional Chinese medicine. Abstract : Rhizoma Paridis saponins (RPS) as active parts of P. polyphylla Smith var. yunnanensis has been used as an anti-cancer drug in traditional Chinese medicine. In this study, RPS was first found to demonstrate a potent effect on markedly reducing the pain induced by cancer. Therefore, the aim of this study was to further explore the analgesic effect of RPS and its possible reaction pathway on H22 hepatocarcinoma cells inoculated in the hind right paw of mice. Cancer-induced pain model mice were randomly divided into 5 groups ( n = 10) and orally administered with RPS (50–200 mg kg −1 ) for 2 weeks. On the last day of treatment, the pain behavior of mice was measured using hot-plate test and open field test, and brain tissues were sampled for detection of biochemical indices, malondialdehyde (MDA), superoxide dismutase (SOD), prostaglandin E2 (PGE2), serotonin (5-HT) and β-endorphin (β-EP). Moreover, the concentrations of NF-κB and IL-1β in the blood serum were measured by ELISA reagent kits. In addition, naloxone, the non-selective antagonist of opioid receptors, was used to identify the opioid receptors involved in RPS's action. It has been found that RPS alleviates cancer pain mainly via the suppression of inflammatory pain induced by oxidative damage, such as decreasing MDA and PGE2 levels, renewing activity of SOD, as well as increasing 5-HT and β-EP in the brain and suppressing the expression of NF-κB and IL-1β in the serum in a concentration-dependent manner. Overall, the current study highlights that RPS has widespread potential antinociceptive effects on a mouse model of chronic cancer pain, which may be associated with the peripheral nervous system and the central nervous system.